Energy and the environment : the oil producers' viewpoint. - Al-Fathi, Saadalla A. (1991)
Notes that in the debate on the environment, the interest of producers is often ignored. Proposes that responsibility for implementing measures designed to restrict greenhouse gas emissions should be shared equally between producers and consumers.